Comparison of autogenous cancellous bone grafting and extra-corporeal shock wave therapy on osteotomy healing in the tibial tuberosity advancement procedure in dogs - Barnes, K.; Lanz, O.; Werre, S.; Clapp, K.; Gilley, R. (Veterinary and Comparative Orthopaedics and Traumatology, 2015)
Objectives: To compare optical values in the osteotomy gap created after a tibial tuberosity advancement (TTA) treated with autogenous cancellous bone graft, extracorporeal shock wave therapy, a combination of auto-genous cancellous bone graft and extra -corporeal shock wave therapy, and absence of both autogenous cancellous bone graft and extracorporeal shock wave therapy using densitometry.Methods: Dogs that were presented for surgical repair of a cranial cruciate ligament rupture were randomly assigned to one of four groups: TTA with autogenous cancellous bone graft (TTA-G), TTA with autogenous cancellous bone graft and extracorporeal shock wave therapy (TTA-GS), TTA with extracorporeal shock wave therapy (TTA-S), and TTA with no additional therapy (TTA-O). Mediolateral radiographs at zero, four and eight weeks after surgery were evaluated to compare healing of the osteotomy gap via densitometry. An analysis of variance was used to compare the densitometric values between groups.Results: At four weeks after surgery, a significant difference in osteotomy gap density was noted between TTA-GS (8.4 millimetres of aluminium equivalent [mmAleq]) and TTA-S (6.1 mmAleq), and between TTA-GS (8.4 mmAleq) and TTA-O (6.4 mmAleq). There were no significant differences noted between any groups at the eight week re-evaluation.Clinical significance: There were no significant differences in the osteotomy gap density at eight weeks after surgery regardless of the treatment modality used. The combination of autogenous cancellous bone graft and extracorporeal shock wave therapy may lead to increased radiographic density of the osteotomy gap in the first four weeks after surgery. Densitometry using an aluminium step wedge is a feasible method for comparison of bone density after TTA in dogs.
Keywords: Tibial tuberosity advancement; TTA; extra -corporeal shock wave therapy; cranial cruciate ligament rupture; autogenous cancellous bone graft